REDESIGN OF JOINT BUSINESS GROUP MANAGEMENT (KUBE) THROUGH DEVELOPMENT OF GROUP SOCIAL COMPANION MODELS - YUSNITA, MAYA (Department of Management, 2019)
This study aims to develop a social companion model of the Joint Business Group (KUBE). There were 50 research respondents consisting of KUBE management and assistants in Pangkalpinang. The research method uses a mixed approach. Based on the results of the study, the KUBE social companion model that was developed is the professional assistance model, which starts with the process of selective recruitment of KUBE companions based on competency, followed by training, as well as the obligation to report KUBE developments periodically. In addition, this research produced the following findings: (1) 67% of training had an impact on companion skills; (3) There is a gap between the supply material and the companion needs by 50%; (4) It is necessary to improve the quality of the accompanying supplies both in terms of material, method, duration of implementation, instructor and training media; and (5) 58% of KUBE management felt that the mentor was able to help KUBE activities.